Capacitance Distribution Analysis Using Wire Mesh Sensor 16×16: - Linahtadiya Andiani; Amaliyah R.I Utami (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
The Wire Mesh Sensor (WMS) is a tomography-based sensor that generates an image of the free space distribution in multiphase flow. The resulting distribution image can be the capacitance distribution pattern is detected by the electrode, which is dependent on the fluid parameters. Based on the concepts, the system may be an alternative option for the early detection of waterways. The goal of this study is to evaluate the performance of the WMS system in an industrial exhaust pipe. The ability of the system to identify fluids is determined using the capacitance distribution analysis from the WMS measurement. An exhaust pipe is modeled as a cylinder phantom and simulated to visualize the capacitance distribution. The WMS technique is used on a phantom made up of a homogeneous and inhomogeneous medium with changing fluid differences. The capacitance distribution of each fluid in the phantom is different. It is caused by differences in the relative permittivity of each fluid. The performance of the WMS system is evaluated by looking at the capacitance distribution changed as the geometry of the fluid volume varied. Based on the results, the WMS system is shown to be capable of easily distinguishing variations in fluid volume percentage.